Maternal and Perinatal Outcome in Teenage Vs. Vicenarian Primigravidae - A Clinical Study - Dutta, Indranil (Journal of clinical and diagnostic research, 2013)
The aim of this study was to evaluate the maternal and foetal outcomes and complications in teenage primigravida as compared to those in primigravidae who were aged 20-29 years. Eighty teenage and one hundred sixty adult primigravidae were taken up for the study. Study duration was 24 months, from November 2010 to October 2012, at Rural Medical Research Centre in southern India. During this period, all cases were included in the study, irrespective of their booking statuses. For every teenage primigravidae, two subsequent adult primigravidae were correspondingly studied. Patients with major skeletal deformities such as kyphoscoliosis, polio, pelvic fractures, diabetes mellitus, renal disorders, morbid obesity were excluded. All cases of molar pregnancies and primigravidas who were admitted for abortions were also excluded. 38.75% of teenage primigravidae were unbooked as compared to 6.9% of adults. 68.75% of teenage primigravidae were anaemic as compared to 33.75% of adults. Antenatal complications like anaemia, hypertensive disorders of pregnancy, oligohydroamnios, hypothyroid were significantly more in teenagers (68.8%) as compared to those which were seen in adults(18.1%). 25% of teenagers had preterm births as compared to 5% adults who has preterm births. 43.75% of teenagers had Lower Segment Caesarean Section (LSCS) as compared to 20% adults who had LSCS. Indication was foetal distress in a majority of teenagers (68.5%). 29.2% of teenagers had low birth weight children as compared to 16.6% adults who had such children. 31.7% of teenage neonates required NICU admissions as compared to 12.27% neonates of adult mothers. It can be interpreted that teenage primigravidae had a significant number of complications in pregnancy, leading cause being anaemia, more preterm incidences and higher rates of LSCS, followed by higher number of NICU admissions. Since teenage pregnancy is a multifaceted problem, it demands multidimensional solutions. Teenage pregnancies are more common in populations with low socio-economic statuses, due to lack of education, awareness of complications of teenage pregnancies, and various other factors. Hence, awareness should be created and various programmes should be taken up, to educate mainly the poor in our rural setup. As early marriages cannot be prevented in our culture, so, possibly creating awareness on late conceptions is of utmost importance.